Mitochondria-Targeting Anticancer Metal Complexes - Erxleben, Andrea (Current Medicinal Chemistry, 2019)
Background: Since the serendipitous discovery of the antitumor activity of cisplatin there has been a continuous surge in studies aimed at the development of new cytotoxic metal complexes. While the majority of these complexes have been designed to interact with nuclear DNA, other targets for anticancer metallodrugs attract increasing interest. In cancer cells the mitochondrial metabolism is deregulated. Impaired apoptosis, insensitivity to antigrowth signals and unlimited proliferation have been linked to mitochondrial dysfunction. It is therefore not surprising that mitochondria have emerged as a major target for cancer therapy. Mitochondria-targeting agents are able to bypass resistance mechanisms and to (re-) activate cell-death programs. Methods: Web-based literature searching tools such as SciFinder were used to search for reports on cytotoxic metal complexes that are taken up by the mitochondria and interact with mitochondrial DNA or mitochondrial proteins, disrupt the mitochondrial membrane potential, facilitate mitochondrial membrane permeabilization or activate mitochondria-dependent celldeath signaling by unbalancing the cellular redox state. Included in the search were publications investigating strategies to selectively accumulate metallodrugs in the mitochondria. Results: This review includes 241 references on antimitochondrial metal complexes, the use of mitochondria-targeting carrier ligands and the formation of lipophilic cationic complexes. Conclusion: Recent developments in the design, cytotoxic potency, and mechanistic understanding of antimitochondrial metal complexes, in particular of cyclometalated Au, Ru, Ir and Pt complexes, Ru polypyridine complexes and Au-N-heterocyclic carbene and phosphine complexes are summarized and discussed.
Keywords: apoptosis